Inhibitory mechanism of vortioxetine on CYP450 enzymes in human and rat liver microsomes - Zhan, Yunyun; Wang, Anzhou; Yu, Yige; Chen, Jie; Xu, Xinhao; Nie, Jingjing; Lin, Jingjing (Frontiers in Pharmacology, 2023)
Vortioxetine is a novel anti-major depression disorder drug with a high safety profile compared with other similar drugs. However, little research has been done on drug-drug interactions (DDI) about vortioxetine. In this paper, the inhibitory effect of vortioxetine on cytochrome P450 (CYP450) and the type of inhibitory mechanism were investigated in human and rat liver microsomes. We set up an in vitro incubation system of 200 µL to measure the metabolism of probe substrates at the present of vortioxetine at 37°C. The concentrations of the metabolites of probe substrates were all measured by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method. It was found no time-dependent inhibition (TDI) of vortioxetine through determination of half-maximal inhibitory concentration (IC50) shift values. The enzymes and metabolites involved in this experiment in human and rats were as follows: CYP3A4/CYP3A (midazolam); CYP2B6/CYP2B (bupropion); CYP2D6/CYP2D (dextromethorphan); CYP2C8/CYP2C-1 (amodiaquine); CYP2C9/CYP2C-2 (losartan); and CYP2C19/CYP2C-3 (mephenytoin). We found that vortioxetine competitively inhibited CYP2C19 and CYP2D6 in human liver microsomes (HLMs) with inhibition constant (Ki) values of 2.17 µM and 9.37 µM, respectively. It was noncompetitive inhibition for CYP3A4 and CYP2C8, and its Ki values were 7.26 µM and 6.96 µM, respectively. For CYP2B6 and CYP2C9, vortioxetine exhibited the mixed inhibition with Ki values were 8.55 µM and 4.17 µM, respectively. In RLMs, the type of vortioxetine inhibition was uncompetitive for CYP3A and CYP2D (Ki = 4.41 and 100.9 µM). The inhibition type was competitive inhibition, including CYP2B and CYP2C-2 (Ki = 2.87 and 0.12 µM). The inhibition types of CYP2C-1 and CYP2C-3 (Ki = 39.91 and 4.23 µM) were mixed inhibition and noncompetitive inhibition, respectively. The study of the above mechanism will provide guidance for the safe clinical use of vortioxetine so that the occurrence of DDI can be avoided.